Reactivation of VX-Inhibited Human Acetylcholinesterase by Deprotonated Pralidoxime. A Complementary Quantum Mechanical Study - da Silva, Jorge Alberto Valle; Pereira, Ander Francisco; LaPlante, Steven R; Kuca, Kamil; Ramalho, Teodorico Castro; França, Tanos Celmar Costa (Biomolecules, 2020)
In the present work, we performed a complementary quantum mechanical (QM) study to describe the mechanism by which deprotonated pralidoxime (2-PAM) could reactivate human (Homo sapiens sapiens) acetylcholinesterase (HssAChE) inhibited by the nerve agent VX. Such a reaction is proposed to occur in subsequent addition-elimination steps, starting with a nucleophile bimolecular substitution (SN2) mechanism through the formation of a trigonal bipyramidal transition state (TS). A near attack conformation (NAC), obtained in a former study using molecular mechanics (MM) calculations, was taken as a starting point for this project, where we described the possible formation of the TS. Together, this combined QM/MM study on AChE reactivation shows the feasibility of the reactivation occurring via attack of the deprotonated form of 2-PAM against the Ser203-VX adduct of HssAChE.
Keywords: VX; Molecular Dynamics Simulation; Acetylcholinesterase; protony; molekulární konformace; Organothiophosphorus Compounds; organothiofosforové sloučeniny; Quantum Theory; serin; lidé; acetylcholinesterase; Pralidoxime Compounds; simulace molekulární dynamiky; Molecular Conformation; pralidoximové sloučeniny; katalytická doména; acetylcholinesterasa; Serine; Protons; QM/MM method; 2-PAM; kvantová teorie; Catalytic Domain; Humans